Forehand and Backhand Tennis Exercises: Study Literature Review - Rices Jatra; Alnedral; Kamal Firdaus (Indonesian Journal of Physical Education and Sport Science, 2023)
Study purpose. The sport of tennis is one of the most popular branches globally and there are various techniques in hitting tennis. The purpose of this article review is to find out about exercises to improve groundstroke ability in tennis in Indonesia. The research method uses a literature review (Study Literature Review).